Research handbook on accounting and ethics - Brivot, Marion; Cho, Charles H. (Research handbooks on accounting series, 2023)
"This Research Handbook focuses on the collective ethical issues facing the accounting profession, as well as the users of services provided by accountants today. Providing an overview of contemporary accounting and ethics issues around the world, the Research Handbook on Accounting and Ethics discusses the ethical considerations involved in each of the major areas of activity in accounting, including external and internal auditing, tax, forensic accounting, and governance. Chapters feature discussions on the ethical implications of artificial intelligence and data analytics in accounting, the effectiveness of anti-corruption agencies in Africa, and accounting ethics education in Hong Kong and Macau. It also proposes new areas of research relating to accounting and ethics, through cross-fertilization with other disciplines and presenting multiple innovative perspectives. Offering discussions on a wide range of topics and research methods, this Research Handbook will be essential reading for students and scholars in accounting ethics, and business ethics. Accounting standards setters, policymakers, practitioners, and regulators will find this a useful resource for encouraging reflection on the ethical ramifications of their professional duties"--